Alterações e lesões de mucosa bucal na população urbana e rural de Ouro Preto, Minas Gerais, 2003 - Herminia Marques Capistrano (2005)
A cross-sectional survey was performed to determine the prevalence and associated factors of all the oral mucosal conditions, as lesions as alterations, present in the urban and rural population in Ouro Preto, Brazil. A random sample of the full population was obtained (n=777) stratified in four age range, about 50% male and 50% female and half in the urban and half in the rural locations. Data were collected through an interview and clinical exams, by trained and calibrated examiners The interview was made to get information about socio demographic and health conditions, toxic habits (tobacco and alcohol), professional sun exposition and health servicxe access. Oral examination was performed to detect all oral mucosal conditions presents, pathological or not. One or more oral mucosal conditions were found in 574 inhabitants (70,4%) of whom 244 (31,4) had one or more lesions and 518 (66,6%) had one or more alterations. No statical significant difference was observed in urban and rural population for prevalence of oral mucosal conditions. The most common lesions were denture stomatitis (9,7%), frictional keratosis (3,7%), denture-induced hyperplasia (3,6%) nodular hyperplasia (2,4%), actinic cheilitis (2,3%) chronic abscess (1,5%), and angular cheilitis (1,2%). Leukoplakia had 1,0% of ocurrence, eritoplakia 0,3% and oral cancer 0,3% and all patients are smokeless-tobacco users. Different factors increased significantly the prevalence of specific lesions. People aged 60 years (OR=4,1), removable denture wearers (OR=3,8) smokeless tobacco users (OR=1,9) and lack of sewerage system (OR=1,6), had the highest odds of having a lesion. The six more prevalement alterations and risk factors statistically associated are: coated tongue (47,4%), melanin pigmentation (46,6%), tongue variscosties (32,9%), leukodema (17,8%) Fordyce granules ((15,5%) and fissured tongue (14,3%). The most relevant risk factor for alterations were aging, with greatest risk for people aged 40-59 years (OR=3,9) and 60 or more years (OR=3,3). The prevalence of oral mucosal conditions in this population is high. With the exception of aging, all factors involved are avoidable and changed, suggesting the necessity of educative and preventive oral health actions to prevent lesions and control of the risk factors.